Analysis of Polygala tenuifolia Transcriptome and Description of Secondary Metabolite Biosynthetic Pathways by Illumina Sequencing - Hongling Tian; Xiaoshuang Xu; Fusheng Zhang; Yaoqin Wang; Shuhong Guo; Xuemei Qin; Guanhua Du (International Journal of Genomics)
Radix polygalae, the dried roots of Polygala tenuifolia and P. sibirica, is one of the most well-known traditional Chinese medicinal plants. Radix polygalae contains various saponins, xanthones, and oligosaccharide esters and these compounds are responsible for several pharmacological properties. To provide basic breeding information, enhance molecular biological analysis, and determine secondary metabolite biosynthetic pathways of P. tenuifolia, we applied Illumina sequencing technology and de novo assembly. We also applied this technique to gain an overview of P. tenuifolia transcriptome from samples with different years. Using Illumina sequencing, approximately 67.2% of unique sequences were annotated by basic local alignment search tool similarity searches against public sequence databases. We classified the annotated unigenes by using Nr, Nt, GO, COG, and KEGG databases compared with NCBI. We also obtained many candidates CYP450s and UGTs by the analysis of genes in the secondary metabolite biosynthetic pathways, including putative terpenoid backbone and phenylpropanoid biosynthesis pathway. With this transcriptome sequencing, future genetic and genomics studies related to the molecular mechanisms associated with the chemical composition of P. tenuifolia may be improved. Genes involved in the enrichment of secondary metabolite biosynthesis-related pathways could enhance the potential applications of P. tenuifolia in pharmaceutical industries.